2020
DOI: 10.1101/2020.03.12.20034686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics of 34 Children with Coronavirus Disease-2019 in the West of China: a Multiple-center Case Series

Abstract: Background Up to 9 March, 2020, 109577 patients were diagnosed with

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 6 publications
1
29
0
1
Order By: Relevance
“…We found 11 case series, including a total of 333 children (range 6-171 children) with confirmed SARS-CoV-2 infections (Tables 1-4). [7][8][9][10][11][12][13][14][15][16][17] All of the series are from China. One case series included only infants 13 and one only children who were admitted to an intensive care unit.…”
Section: Pediatric Case Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 11 case series, including a total of 333 children (range 6-171 children) with confirmed SARS-CoV-2 infections (Tables 1-4). [7][8][9][10][11][12][13][14][15][16][17] All of the series are from China. One case series included only infants 13 and one only children who were admitted to an intensive care unit.…”
Section: Pediatric Case Seriesmentioning
confidence: 99%
“…Three studies reported incubation periods which varied between 2 and 25 days (mean 7 days, median 6 and 11 days, respectively). 9,15,16 Several studies reported that the nasopharyngeal or throat swabs can be positive before the onset of symptoms. 7,11,14 However, false-negative swabs have also been described.…”
Section: Pediatric Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of more than 2000 child patients with suspected or confirmed COVID‐19 in Hubei, China, found that over 90% presented as asymptomatic or with mild to moderate symptoms 9 . A summary of paediatric cases reported with COVID‐19 is presented in Table 1 7,9‐45 . These numbers are likely to be under‐representative, as there is not universal testing of the whole population for the presence of COVID‐19.…”
Section: Covid‐19mentioning
confidence: 99%
“…17 Numerous smaller case series have found the same types of symptoms occurring at similar rates. [18][19][20] A series of six children from Wuhan in China found all six had fever and four of the six had vomiting. Median recovery time was 7.5 days, and one of the six children required admission to intensive care.…”
Section: Symptomsmentioning
confidence: 99%